Development of GeoGebra-Based Module to Enhance Students’ Understanding of Form Two Circles - Foo, Chuan Hui; Ng, Eric Ching Siang (Journal of Science and Mathematics Letters, 2022)
The purpose of this study is to develop a GeoGebra-based module on Form two Circle topic and to assess the students’ needs for the module, the validity and usability of the module from the perspective of experts, students, and teacher trainees. The experts that were made up of upper form senior subject teachers, lower form senior subject teachers, and outstanding teachers in the subject of Mathematics were elected. Meanwhile, the students and teacher trainees were selected by simple random sampling. There are three phrases in this study namely needs analysis study, validity study, and also usability study. For the needs analysis study, 45 Form two students were chosen to be the respondent. Among them, 15 were sampled for the pilot study and another 30 for the real study. A total of 73.33% of respondents faced difficulties in understanding the concept of the Circle topic and 70.00% of respondents suggested that there is a need for the development of a GeoGebra-based module for the Circle topic. For the validity study, three experts were elected to assess the validity index. Content validity index and kappa statistics of 1.00 were obtained. This proved that the module has high validity. For the usability study, 45 teacher trainees were chosen as the respondents. 15 of them were sampled for the pilot study and another 30 for the real study. The average of four Likert scales for usability study is 3.6044. This proved that the module has high usability index. In conclusion, this study successfully developed a GeoGebra-based module with high validity and usability index. The development of this GeoGebra-based module is believed to improve the teaching practices among educators and enhance students’ understanding of the Form 2 Circle topic.